Biomechanical jumping differences among elite female handball players with and without previous anterior cruciate ligament reconstruction: a novel inertial sensor unit study - Setuain, I.; Millor, N.; González-Izal, M.; Gorostiaga, E. M.; Gómez, M.; Alfaro-Adrián, J.; Maffiuletti, N. A.; Izquierdo, M. (Sports Biomechanics, 2015)
Persistent biomechanical and jumping capacity alterations have been observed among female athletes who have sustained anterior cruciate ligament (ACL) injuries. The purpose of this study was to examine if biomechanical jumping differences persist among a cohort of elite female handball players with previous ACL reconstruction several years after return to top-level competition. In order to achieve this goal, a direct mechanics simplified analysis by using a single Inertial Sensor Unit (IU) was used. Twenty-one elite female (6 anterior cruciate ligament reconstructed and 15 uninjured control players) handball players were recruited and evaluated 6.0 ± 3.5 years after surgical anterior cruciate ligament reconstruction. Bilateral and unilateral vertical jumps were performed to evaluate the functional performance and a single inertial sensor unit was employed in order to collect 3D acceleration and 3D orientation data. Previously ACL-reconstructed analysed athletes demonstrated significant (p < 0.05) alterations in relation to the three-dimensional axis (X-Y-Z) supported accelerations and differing jump phase durations, including jumping performance values, in both bilateral and unilateral jumping manoeuvres several years after ACL reconstruction. Identification of the encountered deficits through the use of an IU devise could provide clinicians with a new reliable tool for movement analysis in a clinical setting.